Prisoner Development as an Effort to Reduce Criminality: A Case Study at Class IIB Merauke Correctional Facility - Tajuddin, Mulyadi (Jurnal Ilmu Hukum Kyadiren, 2025)
This study aims to analyze the implementation of inmate coaching patterns in reducing post-release criminality at the Class IIBMerauke Correctional Institution. The research method used is a sociological juridical approach, using primary and secondary data collected through document searches and literature research. The results showed that the pattern of coaching of prisoners inMerauke Class IIB Correctional Institution refers to the legal basis such as Law No. 22 of 2022 concerning Corrections and related regulations. Coaching is carried out through initial, advanced, and final stages which include personality development and independence development. Spiritual development is the main focus and has had a positive impact in reducing the post-releasecrime rate. However, there are several factors inhibiting the success of coaching, including overcrowding and stigmatization from the community.